PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CSR DAN GCG SEBAGAI VARIABEL PEMODERASI (Studi Perusahaan Manufaktur Industri Sektor Basic Industry and Chemicals yang Terdaftar di BEI tahun 2020-2022) - Sumarsono, Vicky; Laksito, Herry (Diponegoro Journal of Accounting, 2024)
This study examines the impact of financial performance on firm value, moderated by Corporate Social Responsibility (CSR) disclosure and Good Corporate Governance (GCG). Focusing on manufacturing companies in the Basic Industry and Chemicals sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022, firm value is measured by Tobin’s Q and financial performance by Return on Assets (ROA). The moderating variables are evaluated through the independence of the board of commissioners and the Corporate Social Responsibility Index. Using purposive sampling, 15 companies were selected and analyzed with multiple linear regression. The findings, based on stakeholder theory, highlight the importance of financial performance, CSR, and GCG in enhancing firm value.